Innovation in the Second-Generation Curriculum " Arabic Language Book for the Fourth Year of Middle School" - Aouadj, Halima; Mebrak, Houcine (Journal of Human Sciences, 2020)
Arab linguists interested in teaching Arabic language sciences and literature and therefore allocated a wide area in the curriculum and educational programs, especially in light of the major challenges imposed by globalization with its cognitive momentum and scientific development, and therefore it is necessary to keep up with our educational system for this In order to build a healthy human being who is balanced in his thinking and personality, which is associated with science and culture that is immune to awareness and education, our educational system has abandoned the old approaches and initiated the application of the approach with competencies that are in line with the spirit of the time.